Manifestasi Kulit pada Penyakit Sistemik : Literature Review - Debrin Gradischerline; Hapsari Triandriyani; Hadi Firmansyah (Pusat Riset dan Inovasi Nasional, 2026)
The skin is an organ that often shows clinical changes due to systemic disorders. This study presents a literature review on skin manifestations in various metabolic, autoimmune, neoplastic, endocrine, and infectious diseases. Data were obtained from national and international scientific articles through structured searches on several databases. The analysis was performed qualitatively to identify the pattern of relationships between internal pathophysiological mechanisms and skin changes. The results of the study show that immunological, vascular, and metabolic disorders have a major contribution to the appearance of certain skin lesions. Skin manifestations also serve as an early indicator of systemic disease so they are important for the process of diagnosis and clinical monitoring. In addition, a variety of specific skin lesions have been shown to correlate with the severity of the disease, so it can be used as a parameter for evaluating the course of the disease and the response of therapy. A comprehensive understanding of the relationship between systemic diseases and skin changes is an important basis for clinicians to take a holistic diagnostic approach and determine more appropriate management strategies. These findings confirm that skin examinations are not only relevant in dermatology, but are also an essential component in the overall assessment of systemic health.